IMMUNOMODULATORY EFFECTS OF CAMELLIA SINENSIS AGAINST COCCIDIOSIS IN CHICKENS - A. Abbas; Z. Iqbal; R. Z. Abbas; M. K. Khan; J. A. Khan; K. Hussain; M. S. Mahmood; H. M. Rizwan (Journal of Animal and Plant Sciences, 2017)
Purpose of current study was to evaluate the immunomodulatory potential of Camellia sinensis in broiler chickens artificially infected with mixed Eimeria species. A total of 108 chickens were equally divided in six groups. Camellia sinensis in powder form was administered in feed in three graded doses (4, 5 and 6%) containing three control groups (positive control, negative control and normal control). Cell mediated immunity was evaluated using Phytohemagglutinin-P (PHA-P) through classical toe-web assay. Humoral response was determined by micro-hemagglutination test using sheep red blood cells. Results of study demonstrated that C. sinensis treatment enhanced cellular and humoral immunity against coccidiosis in dose dependent manner by increasing lymohoproliferative immune response and increased immunoglobulin levels (Total immunoglobulins, IgG and IgM) in broiler chickens. It was concluded from the present study that C. sinensis has a potential to be used as immunomodulatory agent against coccidiosis in broiler chickens.
Keywords: Camellia sinensis; Coccidiosis; Eimeria; Immunomodulation